Four pro-inflammatory cytokines of rohu (Labeo rohita) during early developmental stages, their tissue distribution and expression by leucocytes upon in-vitro stimulation. Issue 2 (December 2015) - Dash, P.; Patel, S.; Dixit, A.; Garg, L.C.; Sahoo, P.K.
Abstract: Cytokines are important components of both adaptive and innate immunity, and are required to initiate and regulate immune responses following infection. The ontogeny and tissue specific distribution of four pro-inflammatory cytokines, interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), IL-8 and IL-1β in rohu ( Labeo rohita ), and their responses by leucocytes from anterior-kidney/head-kidney (HKLs), spleen (SPLs) and peripheral blood (PBLs) following stimulation with concanavalin A (ConA), ConA with phorbol 12-myristate 13-acetate (ConA/PMA) and formalin-killed Aeromonas hydrophila cells (FAH) were studied. In ontogeny study, mRNA levels of IL-6 and IL-1β were evident in unfertilized egg stages of L. rohita whereas IL-8 and TNF-α transcripts were found from 1 to 3 h post-fertilization (hpf) onwards till day 15 post-fertilization, respectively. Basal level of all four cytokines was observed in all twelve tissues (eye, brain, heart, gill, anterior kidney, posterior kidney, spleen, liver, skin, muscle, hindgut and foregut) of L. rohita juveniles. Expression levels of IL-6 and IL-8 were found to be the highest in liver and heart tissues, respectively, while TNF-α transcripts were high in anterior kidney and liver tissues. Transcripts of IL-1β showed high expression in muscle, heart and spleen. Upon in vitro stimulation of leucocytes, there was variable up-regulation of all the four cytokines following different treatments throughout the experimental time period. Induction of cytokines was more pronounced in PBLs stimulated with FAH compared to other stimuli. However, an up-regulated IL-8 expression was evident in all the leucocytes following stimulation with FAH thus indicating IL-8 could be used as an indicator or indirect marker to monitor vaccine status or health status of L. rohita during bacterial infection. Highlights: Ontogeny and tissue specificity of IL-6, TNF-α, IL-8 and IL-1β were studied in rohu. Expression of IL-6 and IL-1β were evident from unfertilized egg stage onwards. IL-8 and TNF-α transcripts were detected from 1 to 3 hpf, respectively. Basal expression of all four cytokines was observed in all twelve major tissues studied. In in vitro study, expression of cytokines was more pronounced in PBLs after bacterial induction.